Propuesta para el aprovechamiento del agua residual generada en la planta de tratamiento de C.I Sigra S.A. (2018)
This project is focused on the development of an alternative for the use of treated wastewater from the WWTP of C.I Sigra S.A. Therefore, a series of activities are carried out, starting with the collection of information regarding the refinery processes of the plant and all the unit operations used in the company's WWTP. In order to diagnose the water consumed in each of the plant processes and characterize the effluent water, to make the most of the approximate 1860 m3 of water per month in the plant.